At a Crossroads: Improving Counselor Training in Spirituality and Religion - Scurry, Jakara (Counseling and values, 2024)
Spirituality and religion are considered components of wellness, important factors in counseling, and associated with improved mental health outcomes (Brown et al., 2013; Dixon & Wilcox, 2016; Kyle, 2013; Myers et al., 2007). The 2016 cacrep standards and the aservic Spiritual Competencies also highlight the need for counselors to be equipped to address clients’ spiritual and religious concerns (aservic, 2009; cacrep, 2015). However, some counselor education programs insufficiently prepare counseling trainees to integrate spirituality and religious practices into sessions with clients (Dailey et al., 2015; Dobmeier & Renier, 2012; Henriksen et al., 2015; Pearce et al., 2019). This article reviews spirituality and religion and their relevancy for counseling and wellness, discusses the 2024 proposed cacrep standards, examines counselor education programs, and provides recommendations for cacrep and counselor education programs to address the deficiencies in counselors’ spiritual training.